Digestibility of Dry Matter and Organic Matter in Feed with Pollard Substitution in Male Jawarandu Goats - Umar, Malikah; Hidayati, Nurul; Purdiyanto, Joko; Agustina, Desi Kurniati (Jurnal Agripet, 2025)
This study aimed to determine the effect of adding pollard to the feed on the digestibility of dry matter and organic matter in Jawarandu goats, as well as to assess the impact of pollard supplementation on the productivity of these goats. The study was conducted from March 2020 to May 2020. The material used in the study consisted of male Jawarandu goats, aged approximately 1 year, with an average body weight of 20.74 kg (CV= 13.60%), placed in individual metabolic cages with a stage cage model, totaling 12 Jawarandu goats. The feed used consisted of forage, specifically elephant grass, and concentrate, comprising rice bran, cassava flour, and pollard, with a ratio of 30% forage to 70% concentrate. This study employed an experimental, quantitative method with a completely randomized design (CRD), involving four treatments. The results showed that the effect of adding pollard to the ration on dry matter and organic digestibility in male Jawarandu goats was not significantly different (P0.05). However, the best treatment in this study was treatment P3 with a pollard addition ratio of 60%, yielding a daily body weight gain of 89.63 g/head/day, dry matter digestibility of 47.5111.55%, and organic matter digestibility of 55.6711.30% in male Jawarandu goats. The addition of pollard to the feed of Jawarandu goats tends to increase the value of dry matter digestibility, organic matter digestibility, and increase the productivity of Jawarandu goats.